2016
DOI: 10.1111/ans.13522
|View full text |Cite
|
Sign up to set email alerts
|

Free‐flap salvage: muscle only versus skin paddle – an Australian experience

Abstract: While timely recognition and re-exploration of the compromised free flap in the early postoperative setting is important in determining the flap salvage success, it is demonstrated that salvage rates are poorer for muscle only flaps compared with flaps with a skin paddle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 17 publications
(17 reference statements)
0
18
1
1
Order By: Relevance
“…The Doppler ultrasound showed regular findings during the entire observation period, as the monitoring is limited to arterial feedback. Arterial thrombosis is significantly less frequent in free tissue transfer [25,40], which also emphasizes the advantages of HSI technology in detecting venous and arterial vascular compromises. Not only does it indicate a vascular problem, but it is also able to distinguish venous from arterial compromise by pattern differentiation as Holmer et al have already described [38].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The Doppler ultrasound showed regular findings during the entire observation period, as the monitoring is limited to arterial feedback. Arterial thrombosis is significantly less frequent in free tissue transfer [25,40], which also emphasizes the advantages of HSI technology in detecting venous and arterial vascular compromises. Not only does it indicate a vascular problem, but it is also able to distinguish venous from arterial compromise by pattern differentiation as Holmer et al have already described [38].…”
Section: Discussionmentioning
confidence: 91%
“…The skin is missing as a reliable predictor of possible vascular complications. In the case of venous thrombosis, for example, Doppler ultrasound continues giving regular sound feedback and abnormal tissue configuration can be prolonged [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Objective evaluations were also absent in the literature mentioning benefits of monitoring skin flap. 40 Dat et al 18 reported that muscle only free-tissue transfer flaps have a lower salvage rate compared with flaps with an overlying skin paddle. In their report, the time to reexploration of the muscle flap was shorter than that of the flap containing the skin paddle muscle flap but it was not significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as the skeletal muscle is more active in metabolism than that of other tissues, it is more vulnerable to tissue ischemia. Therefore, difficulties in flap monitoring can be a major drawback of this reconstruction method …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation